PENYULUHAN TENTANG KESADARAN PENTINGNYA KESEHATAN REPRODUKSI BAGI REMAJA DI DESA HUTA HOLBUNG - lubis, juli ana (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
ABSTRACT Adolescence is a period of transition from early childhood to early adulthood. Reproductive health is a state of complete physical, mental and social well-being and not merely the absence of disease and infirmity, in all matters relating to the reproductive system and its functions and The phenomena of the popularity of female adolescent reproductive health have been discussed and studied more closely, while male adolescent reproductive health has received less attention from society and the youth themselves. This community service activity is carried out to increase adolescent knowledge about the importance of adolescent reproductive health.The problem found was outreach activities about awareness of the importance of adolescent reproductive health because there had not been any counseling. Based on the results of interviews conducted, there were still teenagers who did not know about adolescent reproductive health in Huta Holbung Village.This activity aims to increase the knowledge of adolescents in Huta Holbung Village about the awareness of the importance of reproductive health in adolescents. The results of this activity are changes in adolescent knowledge and awareness of the importance of reproductive health in adolescents Keywords: Adolescents, Reproductive Health